Political memoirs, 1905-1917 - Miliukov, P. N. (Pavel Nikolaevich), 1859-1943.; Mendel, Arthur P. (Ann Arbor, MI : University of Michigan Press, 1967)
"The memoirs of Paul Miliukov, acknowledged leader of the Russian liberals before the Bolshevik revolution, present the most comprehensive, colorful, and personal account of the liberals to establish a constitutional, representative government in Russia. As one of Russia's foremost prerevolutionary historians, Miliukov offers a wealth of information on the failure of this hopeful attempt. (...) He discusses foreign affairs--the Balkan problem, the crisis with Turkey, and the first World War, during part of which he was minister of Foreign Affairs. He relates the attempt to modernize the ponderous, backward systems of rural economy. He recounts the establishment of the Provisional Government in 1917 after the February revolution, his difficulties as a cabinet minister in the government, his forced resignation, the collapse of the liberal government, and the final Bolshevik victory. He also gives vivid portraits of other leading figures during this stormy period--Rasputin and Pobedonostsev, Nicholas II, Kerensky, Witte and Prince Lvov, and Lenin"--publisher
Translation of Vospominaniia.
Donation of Anatole Shub
Keywords: Russia -- Politics and government -- 1894-1917.